(untitled) (Libellarium: journal for research in the field of information and related sciences, 2017)
This paper presents findings of a study based on the concept of information horizons, which was proposed in 1999 by Diane Sonnenwald with purpose of exploration human information behaviour. Sonnenwald suggests in her framework that certain types of data, which have not been traditionally included in studies of information behaviour, are important. These data include when and why people access (or why they do not access) information resources and channels, relationships and interconnectedness among information resources, individual preferences and evaluation of information resources and the impact of contexts and situations on the information seeking process. Since the concept of information horizons includes a mixture of data collection methodologies, this paper brings only the data obtained through information horizon maps. The research described in the paper was conducted in May 2015 in Osijek, Croatia and included ten respondents – five teachers of Croatian language and literature and five physicians. The purpose of the research was to learn how information horizons and information sources they are comprised of differ between observed professions and between two age groups in which we divided the respondents. For the purpose of this research, we used semi-structured interviews using the critical incident technique, map drawing technique, but also a short questionnaire we created. Maps consisted of three concentric circles named Zone 1, 2 and 3 and the sources listed in the maps were weighed accordingly. Our results show that although online and printed sources are widely used by all our respondents, physicians show slight preference for online, whereas teachers for printed resources. Younger respondents tend to use a wider variety of information sources whereas older respondents tend to prefer online sources. This is the first research of information horizons in Croatia, and one of few researches in general that deal with information horizons of members of different professions.